Development of an Excel-VBA Based Decision Support System for Network Engineers - AONI, HUSSEIN (İstanbul Kültür Üniversitesi, 2022)
A router is a hardware component at the heart of any computer network, as it is responsible for connecting a network to other networks in the Internet infrastructure and finding the most efficient way for data packets to reach their destination. Choosing the best router is a critical decision for network engineers because there are so many router brands, brand models, and many criteria that distinguish each router. Due to lack of managerial skills or technical issues, network engineers may choose the wrong router for their network. In this study, a Decision Support System (DSS) based on the Analytical Hierarchy Process (AHP) method, which is a multi-criteria decision making method, has been developed for the selection of the appropriate router. The DSS is built using Visual Basic for Applications (VBA) integrated with Microsoft-Excel. The proposed DSS is a user-friendly XLSM file that can be used on any computer running Microsoft-Excel. The DSS was tested based on four criteria (Cost, Reliability, Efficiency and Port counts) and four brand alternatives (Cisco, Juniper, Huawei and MikroTik). The developed DSS accompanies the decision maker's (DM) comparison process of criteria and the alternative routers according to each criterion, and finally recommends the most suitable router. In addition, if the comparison matrix of DM is inconsistent, the proposed DSS makes minor changes to the original preferences of DM, ensuring a zero inconsistency rate. The proposed method has been tested with data sets published in the literature, and its advantages over other methods to reduce inconsistency have been demonstrated.
Ağ Mühendisleri İçin Excel-VBA Tabanlı Karar Destek Sisteminin Geliştirilmesi
▪ Yüksek lisans tezi.
Keywords: Analytical hierarchy process (AHP); Decision Support System (DSS); Visual Basic for Applications (VBA); Consistency